2014
DOI: 10.1117/12.2046205
|View full text |Cite
|
Sign up to set email alerts
|

Novel EUV resist materials design for 14nm half pitch and below

Abstract: Polymers with a different Tg and activation energy were prepared to clarify influences of acid diffusion on resolution at 15 nm half-pitch (hp) and 14 nm hp using a EUV micro-field exposure tool (MET) at LBNL. Resolution on such a narrow pattern was limited by collapse and pinching. Clear relationship between pinching numbers and polymer Tg indicates that acid diffusion is one of major contributors on the pinching. In addition, polymers with a low thermal activation energy (Ea) on deprotection were effective f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Similarly, we demonstrated LWR advantage of nBA when exposing conventional polarity switch photoresist with 45 nm hp L/S [20]. On the other hand, similar patterning results on both developers have been confirmed when feature size is 20 nm hp and photoresist is cross-linking systems.…”
Section: Efficient Nti Developer Designsupporting
confidence: 64%
See 1 more Smart Citation
“…Similarly, we demonstrated LWR advantage of nBA when exposing conventional polarity switch photoresist with 45 nm hp L/S [20]. On the other hand, similar patterning results on both developers have been confirmed when feature size is 20 nm hp and photoresist is cross-linking systems.…”
Section: Efficient Nti Developer Designsupporting
confidence: 64%
“…In previous work, we revealed that nBA had a clear advantage on dissolution unit grains size and surface smoothness compared to aqueous 2.38% TMAH solution [20]. Similarly, we demonstrated LWR advantage of nBA when exposing conventional polarity switch photoresist with 45 nm hp L/S [20].…”
Section: Efficient Nti Developer Designmentioning
confidence: 93%
“…We have previously reported that combination of a high Tg and low Ea polymer with a large acid provides an apparently better L/S resolution with maintaining sensitivity [10,24]. In this study, we explored the same idea to determine how acid diffusion length contributes to block mask and isolated dot resolution.…”
Section: Influence Of Acid Diffusion Lengthmentioning
confidence: 99%
“…While sensitivity became slightly worse, the total resist performance turned out improved, judged from the Z-factor [3]. Tsubaki et al investigated the dependency of pinching behavior of 15-18 nm HP with low activation energy (Ea) polymer, revealing that pinching was suppressed when the polymer Tg was 40 o C and over higher than the post exposure bake (PEB) temperature [4]. From the chemical structural point of view, methacrylic terpolymers containing various adamantyl polar units were compared by Tanagi et al showing that unit with long alkyl connecting group and two hydroxyl groups gave good resist performance in terms of resolution and line edge roughness (LER) by EB lithography test.…”
Section: Pag Blend Type 211 Polymer Developmentmentioning
confidence: 99%